(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The calculation of subsidence points along the contour and in the center of the tank bottom is complicated in the case of erosion on inhomogeneous, subsidence, damaged soils, mules, flooded and seismically dangerous areas. The article analyzes the most dangerous geological phenomena, processes and complicated geotechnical conditions for the territory of Ukraine. The method of an artificial base arrangement with improved properties due to vertical reinforcement by soil cement elements is considered. Techno-economic comparison of the proposed variant with the usual pile variant of foundations (subsidence soils, estimated seismic intensity of 9 points) has been carried out. Probabilistic analysis of the artificial base has been carried out and the corellation between the probability of its failure from the percentage of reinforcement has been determined.